Low volume polyethylene glycol with ascorbic acid, sodium picosulfate-magnesium citrate, and clear liquid diet alone prior to small bowel capsule endoscopy - Rayner-Hartley, Erin (World J Gastrointest Endosc, 2016)
AIM: To compare low volume polyethylene glycol with ascorbic acid, sodium picosulfate-magnesium citrate and clear liquid diet alone as bowel preparation prior to small bowel capsule endoscopy (CE). METHODS: We retrospectively collected all CE studies done from December 2011 to July 2013 at a single institution. CE studies were reviewed only if low volume polyethylene glycol with ascorbic acid, sodium picosulfate-magnesium citrate or clear liquid diet alone used as the bowel preparation. The studies were then reviewed by the CE readers who were blinded to the preparation type. Cleanliness and bubble burden were graded independently within the proximal, middle and distal small bowel using a four-point scale according to the percentage of small bowel mucosa free of debris/bubbles: grade 1 = over 90%, grade 2 = between 90%-75%, grade 3 = between 50%-75%, grade 4 = less than 50%. Data are expressed as mean ± SEM. ANOVA and Fishers exact test were used where appropriate. P values < 0.05 were considered statistically significant. RESULTS: A of total of 123 CE studies were reviewed. Twenty-six studies were excluded from analysis because of incomplete small bowel examination. In the remaining studies, 39 patients took low volume polyethylene glycol with ascorbic acid, 31 took sodium picosulfate-magnesium citrate and 27 took a clear liquid diet alone after lunch on the day before CE, followed by overnight fasting in all groups. There was no significant difference in small bowel cleanliness (1.98 ± 0.09 vs 1.84 ± 0.08 vs 1.76 ± 0.08) or small bowel transit time (213 ± 13 vs 248 ± 14 ± 225 ± 19 min) for clear liquid diet alone, MoviPrep and Pico-Salax respectively. The bubble burden in the mid small bowel was significantly higher in the MoviPrep group (1.6 ± 0.1 vs 1.9 ± 0.1 vs 1.6 ± 0.1, P < 0.05). However this did not result in a significant difference in diagnosis of pathology. CONCLUSION: There was no significant difference in small bowel cleanliness or diagnostic yield of small bowel CE between the three preparations regimens used in this study.